Making the World a Better Place: Consumers' Group Identity in the Markets with Competition and Two-sided Opportunism - Vesa Kanniainen (Center for Economic Studies and ifo Institute (CESifo), 2016)
Consumer boycotts often provide a disciplinary mechanism against firms deviating from established social norms. Such actions tend to be organized by people through reference groups with a social mission. The intensity of the group identity is, however, private information. Therefore, the membership is the subject of opportunistic free riding. Moreover, opportunism reinforces opportunism in the market transactions as both a deviating and a non-deviating firm can also take the advantage. Despite such limitations on the maintenance of the code of the high ethical conduct, the paper shows that the joint impact competition and the group effect support the profits of firms with a high ethical code. Paradoxically, a strong group identity effect among the consumers may advance the low ethical code as high-cost competitors are not survived. As the monitoring by the consumer groups is focused on large firms these are - against the received wisdom – more likely to adopt the code of the high ethical conduct than the small firms. Pareto-efficient bargaining with the buyers' alliance may not turn out to be an attractive strategy for a firm.
Keywords: D18; D43; L11; 330; consumer boycotts; social identity; market opportunism; competition